PENGARUH BERKARYA SENI 3D MENGGUNAKAN PLAYDOUGH BAGI PERKEMBANGAN KREATIVITAS ANAK USIA 5–6 TAHUN - Wanda Nurjanah; Aini Loita; Herman Syafri (LPPM IAD Probolinggo, 2025)
This study aimed to investigate the effect of three-dimensional (3D) art activities using playdough on the creativity development of children aged 5–6 years. A quasi-experimental design with a pretest–posttest control group was employed, involving 20 children who were evenly divided into experimental and control groups. Data were collected through observation using a validated creativity assessment instrument that measured fluency, flexibility, originality, and elaboration. The experimental group participated in several sessions of 3D art activities with playdough, while the control group received conventional learning without playdough. Data were analyzed using descriptive statistics, the Mann–Whitney U test, and N-Gain calculation. The results revealed a significant increase in creativity scores in the experimental group compared to the control group (p = 0.000). The experimental group achieved an N-Gain score in the medium category, while the control group was in the low category. These findings suggest that 3D art activities with playdough are effective in enhancing children’s creativity by stimulating divergent thinking, strengthening fine motor skills, and fostering self-confidence. The study recommends integrating playdough-based art activities into early childhood education curricula to optimize children’s creative potential. Keywords: playdough; 3D art; creativity; early childhood; quasi-experiment